Editorial - Armstrong , Anona (Journal of Law and Governance, 2015)
Morals, laws and ethics determine what is good or right for human beings and society, what goals people and society ought to pursue, what rules should govern desirable behaviour and what actions they ought to perform. However, they are not the same. Morals are derived from the conventional social norms and expectations that guide behaviour. People of different ethnic backgrounds hold different views about many social norms, such as marriage, the right way to do business, etc. Morals are often associated with the views or precepts of religions. A religion is the set of beliefs, feelings, dogmas and practices that define the relations between human beings and a sacred or divine entity. Religions promise that current behavioiurs will lead to future rewards or punishments.